Immune Responses of Club Cells in Fish: A Review - Dhamayanti, Yeni; Khairunnisa, Hanifa Khansa; Zahrudin, Elham; Bayram, Muhammet; Suciyono, Suciyono (Universitas Airlangga, 2024)
The primary line of defense against pathogens from the environment is often fish epidermis tissue. Nevertheless, little is understood about the physiological mechanisms that underlie the non-specific and/or specific protection that these cells can offer. The exact nature of the relationship between the evolution of ostariophysan fish club cells and chemical warning signals is still unknown and controversial. Fish epidermis layer cells comprise mucus cells, lymphocytes, macrophage cells, cuboidal and squamous epithelial cells, and cells specific to certain fish species. Club cells, also called